The Study Of Utilization Of Steel Slag To Sabodam - Jati Iswardoyo (JURNAL TEKNIK HIDRAULIK, 2016)
Steel slag is one of the results of the rest of smelting iron ore/ steel. To reduce the abundance of steel slag, this study seeks to examine utilization as a substitute for gravel in the concrete used for construction sabodam.The durability of concrete on the outer layer was analyzed by using the results of several studies related.The most influential factor is the compressive strength of bump (impact) as a representation of the clash due to lava rock.It will be discussed about the potential use and durability. To analyze the stability of the sabodam, researcher use SNI 2851: 2015 about Sediment Retention Building Design. The parameter used is the stability of the tilting, sliding and bearing capacity. For alternative use sabodams core material, researcher used split stones and steel slagconcrete. The flood scenarios can be divided into two, namely flood plain and flood lava. Based on the results obtained, the potential for instability is found in the parameters of carrying capacity. Thesabodamwhich using split stones, the bearing capacity of the land has a minimum strength is worth -0.98 kN/m2 (for flood) and -0.43 kN/m2 (for lava flood), while sabodam with steel slag has a minimum strength of 1.74 kN/m2 (for flood) and 1.57kN/m2 (for lava flood) which means notensile stresses occured. The conclusion is the concrete with steel slag can be used as material for sabodam.